The influence of inflammation and hematocrit on clot strength in canine thromboelastographic hypercoagulability. Issue 1 (24th November 2017) - Marschner, Clara B.; Wiinberg, Bo; Tarnow, Inge; Markussen, Bo; Kühnel, Line; Bochsen, Louise; Kristensen, Annemarie T.
Abstract: Objective: To investigate parameters causing canine thromboelastographic hypercoagulability and to investigate whether thromboelastography (TEG) with Cytochalasin D (Cyt D) added is related to parameters of platelet activity. Design: Prospective observational study on hemostatic and inflammatory parameters. Data were collected between November 2012 and July 2013. Setting: University teaching hospital. Animals: Twenty‐eight dogs suffering from diseases predisposing to thrombosis and 19 clinically healthy dogs. Diseased dogs were enrolled if they fulfilled inclusion criteria regarding age, size, informed client consent, and obtained a diagnosis of a disease that has been associated with thrombosis or hypercoagulability. Interventions: None. Measurements and Main Results: Parameters of coagulation and anticoagulation, fibrinolysis, and antifibrinolysis, platelet activity, inflammation, platelet count, and hematocrit were measured using CBC, TEG, platelet aggregation on multiplate, platelet activity on flow cytometry, and hemostatic and inflammatory markers on plasma and serum analyses. ANOVA and multilinear regression analyses indicated that especially hematocrit and the inflammatory parameters C‐reactive protein and interleukin‐8 showed best association with overall clot strength in diseased dogs with hypercoagulable TEG tracings. Ratios presumed to reflect platelet contribution to the TEG tracing obtained in TEG analyses with Cyt D were related especially with hematocrit and P‐selectin expression of platelets measured after γ‐Thrombin activation on flow cytometry. Conclusion: Overall clot strength in TEG analyses of the hypercoagulable dogs included in the present study appears to be primarily associated with inflammation as well as hematocrit. Furthermore, the ratio between standard TEG analyses and TEG analyses with Cyt D may reflect some degree of platelet activity.